2017
DOI: 10.4103/ejd.ejd_191_16
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and knowledge of isolation in operative field among undergraduate dental students

Abstract: Objective:The purpose of this study was to evaluate the general attitude of undergraduate dental students toward rubber dam use, specifically focusing on operative procedures before starting to serve community.Methods:Questionnaires were distributed to undergraduate clinical years' students of two private colleges; Al-Farabi Dental College, Riyadh, KSA and Buraidah Private Colleges, Qassim, KSA. Questions were asked about areas where the students used rubber dam in operative procedures, in which types of carie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
3
16
2
Order By: Relevance
“…15 Investigations among dental students, using questionnaires as a research instrument, are often conducted as a helpful tool to identify their knowledge and perceptions of the rubber dam, as well as to reveal potential problems in the educational process. [22][23][24][25]29 In the present study, all students that regularly attended theoretical courses confirmed that during lectures they have learned about the rubber dam and its advantages. Apart from restorative dentistry and endodontics, attention to rubber dam was given also in pediatric dentistry lessons, indicating the necessity of using the rubber dam in pediatric patients as well.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…15 Investigations among dental students, using questionnaires as a research instrument, are often conducted as a helpful tool to identify their knowledge and perceptions of the rubber dam, as well as to reveal potential problems in the educational process. [22][23][24][25]29 In the present study, all students that regularly attended theoretical courses confirmed that during lectures they have learned about the rubber dam and its advantages. Apart from restorative dentistry and endodontics, attention to rubber dam was given also in pediatric dentistry lessons, indicating the necessity of using the rubber dam in pediatric patients as well.…”
Section: Discussionsupporting
confidence: 73%
“…Various results could be found in the literature with regards to the students' use of rubber dam on adult patients. In Saudi Arabia, dental students used rubber dam almost always, 29 while in Ireland and the UK the majority of students used rubber dam occasionally. 22 When it comes to pediatric patients, more consistent findings were reported -the rubber dam was used rarely or never.…”
Section: Discussionmentioning
confidence: 99%
“…in a study at private dental colleges in Buraidah observed that students in both institutes agreed with the opinions that rubber dam is needed for proper isolation in operative procedures. [ 11 ] They further observed that restoration placed under rubber dam have a superior durability than those not placed with rubber dam was preferred reply by most of the students of both the colleges (99% and 97.8%). Further longitudinal studies that follow up restorations done with and without rubber dam may enlighten this faction expansively.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, the rubber dam has become an essential component of modern adhesive dentistry, 2‐4 as it provides moisture control, improves access and visibility, and enhances time and treatment efficiency 1,2,5,6 . Furthermore, rubber dam improves cross‐infection control, provides an aseptic field, prevents the ingestion or aspiration of foreign objects, and protects and retracts the surrounding tissues 7‐9 …”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,6 Furthermore, rubber dam improves cross-infection control, provides an aseptic field, prevents the ingestion or aspiration of foreign objects, and protects and retracts the surrounding tissues. [7][8][9]…”
mentioning
confidence: 99%